Enhancing biohydrogen yield from corn stover by photo fermentation via adjusting photobioreactor headspace pressure. (February 2023) - Xiang, Guanning; Zhang, Huan; Li, Yameng; Liu, Hong; Zhang, Zhiping; Lu, Chaoyang; Zhang, Quanguo
Graphical abstract: Highlights: Effect of headspace pressure on photosynthetic hydrogen production was reported. Reducing the headspace pressure properly could increase hydrogen yield. The maximum biohydrogen yield of 546.57 mL was obtained at 30 kPa. Cumulative hydrogen yield of experiments could be fitted well by Gompertz model. Abstract: In this study, the effect of bioreactor headspace pressure regulation on photo-fermentative hydrogen production (PFHP) from corn stover (CS) was investigated. The results showed that the headspace pressure could significantly affect the performance of PFHP. With the decrease in the reactor headspace pressure (100 kPa–10 kPa), cumulative biohydrogen production first increased and then decreased, the maximum hydrogen yield of 546.57 mL was obtained at the headspace pressure of 30 kPa. The parameters of Gompertz model showed a lower hydrogen partial pressure was beneficial to speed up the reaction process and shorten the hydrogen production delay time of the system, however, too low pressure would inhibit the metabolism of microorganisms in the PFHP process, resulting lower hydrogen yield obtained.